Clinical utility of commonly used neurocognitive tests in assessing occupational performance in functional capacity evaluation. - Thandrand, Narishca Doorasamy (My University, 2021)
The clinical utility of neurocognitive standardised tests in functional capacity evaluations is essential to the assessment being valid, reliable, evidence-based and client-centred. While conventional bottom-up standardised tests appear to be popular, a growing body of research supports performance-based top-down standardised tests to obtain functional indicators of cognition and occupational performance. The purpose of the study was to describe the perceptions of clinical utility of South African occupational therapists using of standardised neurocognitive assessments in conducting functional capacity evaluations. A traditional mixed method convergent design was used. Quantitative data was obtained from a survey (n=38) on commonly used neurocognitive test and the selection criteria being used by OTs. Qualitative data was collected from four focus groups (n=18) on exploring the perceptions of occupational therapists of the value and clinical utility of the tests being commonly used in the field of functional capacity evaluation. Q-Methodology was used in the final stage with a Q-set of 36 statements derived from the focus groups with 51 participants. Q-factor analysis was used to interpret the data. The results of the study mirrored similar research which revealed that bottom-up tests are commonly being used and OTs are in consensus that the results of these tests provide minimal link to function or occupational performance. The participants from the survey, focus groups and Q-sorts agree that most of the tests lack cultural sensitivity, adaptability and validity for the South African demographic. The study revealed that OTs believe a shift toward standardised performance-based testing is needed to assess occupational performance and remain within the OT theoretical framework.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021
Keywords: Occupational therapy; Work capacity evaluation